DUKUNGAN KELUARGA BERHUBUNGAN POSITIF DENGAN KEAKTIFAN LANSIA DALAM MENGIKUTI POSYANDU LANSIA - Ilham Muhammad; Laily Isro’in; Metti Verawati (Universitas Muhammadiyah Ponorogo, 2017)
AbstractCurrently, it is widely known that the family supports for the elderly give significant influence to the presence of elderly for 1 year in posyandu lansia (Elderly Health Center, hereafter – information center and health care support for the elderly). This is due to the elderly active participation in this health care center can improve their healthy optimally. The objective of the study was to explain positive family support in relation to liveliness of elderly to follow posyandu elderlyCenter in Krajan, Grogol Village, SawooSubdistrict, Ponorogo.This is a correlation study in which the subject of the research is purposively chosen by using purposive sampling. The data are collected by using questionnaire, and then the data are analyzed by using T-score counting of 1 year and 6 months of inactivity. Finally, Fisher Exact statistic test is applied as the tabulation.From the result, it is known that among all 62 respondents, there are 8 respondents or approximately 12.9% respondents got good family support and have active participation, and there are 2 respondents or approximately 3.2% respondents got poor family support but have active participation. Whereas, there are 15 respondents or approximately 24.2% respondents got good family support but have passive participation, and there are 37 respondents or approximately 59.7% respondents got poor family support and have passive participation. The results showed that family support was positively associated with elderly leprosy in following posyandu elderly p = 0,004 with α = 0,05.Finally, of this research support positive relation with elderly activeness participate in posyandu elderly expected elderlyIt is expected that the elderly can regularly participate and for the family members, it is expected that they can always give supports for the elderly in order to help them control their health. The weaknesses of this study are the range of responses to support provided by the family during folloe-up posyandu lansia(Elderly health Center) for 1 year because of the different respinden’s memory can trigger the data inaccuracy. Keywords: family support, activity, Elderly Health CenteAbstrakFenomena yang ada dukungan keluarga bagi para lansia mempengaruhi kehadiran lansia selama 1 tahun di posyandu lansia. Sebagaiaman keaktifan lansia dalam posyandu lansia sangat bermanfaat untuk meningkatkan kesehatan secara optimal. Tujuan penelitian adalah untuk menjelaskan dukungan keluarga berhubungan positif dengan keaktifan lansia dalam mengikuti posyandu lansia di dukuh krajan, desa grogol, kecamatan sawoo, Kabupaten ponorogo.Desain penelitian menggunakan korelasional dengan mengunakan teknik purposive sampling. Pengumpulan data mengunakan instrument kuisioner dengan pengolahan data mengunakan skor-T dan keaktifan posyandu dengan penghitungan selama 1 tahun 6 kali dalam 1 tahun tidak aktif dan pengolahan data mengunakan uji statistik Fisher ExactHasil penelitian didapatkan dari 62 responden. 8 responden (12,9%) dengan dukungan keluarga baik dengan keaktifan aktif, terdapat 2 responden (3,2%) dengan dukungan keluarga buruk dengan keaktifan aktif. Sedangkan 15 responden (24,2%) dengan dukungan keluarga baik dengan keaktifan tidak aktif, dan terdapat 37 responden (59,7%) dengan dukungan keluarga buruk dengan keaktifan tidak aktif. Hasil menunjukan adanya dukungan keluarga berhubungan positif dengan keaktifan lansia dalam mengikuti posyandu lansia p=0,004 dengan α=0,05.Kesimpulan dari penelitian ini dukungan keluarga berhubungan positif dengan keaktifan lansia dalam mengikuti posyandu lansia diharapkan lansia dapat memanfaatkan posyandu lansia dengan rutin, untuk keluarga lansia diharapkan keluarga lebih memberikan dukungan pada lansia agar kesehatan lansia terpantau dengan baik. Kelemahan penelitian ini adalah rentan terhadap kesalahan informasi dari respon terhadap dukungan yang diberikan keluarga selama mengikuti posyandu lansia selama 1 tahun karena daya ingat responden berbeda-beda ini dapat memicu ketidak akuratan informasiKata Kunci: Dukungan Keluarga, Keaktifan, Posyandu lansia